Molecular basis of attractiveness - Tan, Merlyn Mei Yun (2016)
Environmental enrichment (EE) has been reported to cause varying effects on an organism, especially the brain. This allows observable modified physiology or behaviour in the organism to be studied. Past literature has shown that EE impacts even primitive built-in traits, including making rats more attractive. However, there is little research studying the underlying molecular basis of this occurrence. This study investigates this phenomenon by looking to two closely interlinked circuits, the hypothalamic-pituitary-gonadal (HPG) and hypothalamic-pituitary-adrenal (HPA) axes. HPG is involved in sexual attraction and reproductions while HPA, a stress response system, influences attractiveness through its interaction with HPG axis. Posteroventral Medial Amygdala Nucleus (MePV) and Posterodorsal Medial Amygdala Nucleus (MePD) are involved in HPA and HPG respectively. Immunofluorescence expression of C-Fos, an early immediate gene was used as indication of activity of the region of interest in the brain. In this study, we observed a basal level of HPG and HPA activity in response to immobilisation stress. However, when comparing EE rats to the control rats, there is no significant difference in activation of both regions. This research has shed some ideas on the complex interactions of the HPG-HPA axes and its susceptibility to the environment, allowing for further studies.